Mephedrone (4-Methylmethcathinone): Acute Behavioral Effects, Hyperthermic, and Pharmacokinetic Profile in Rats - Šíchová, Klára; Pinterová, Nikola; Židková, Monika; Horsley, Rachel R.; Lhotková, Eva; Štefková, Kristýna; Vejmola, Čestmír; Uttl, Libor; Balíková, Marie; Kuchař, Martin; Páleníček, Tomáš (Frontiers in Psychiatry, 2018)
Mephedrone (MEPH) is a synthetic cathinone derivative with effects that mimic MDMA and/or cocaine. Our study in male Wistar rats provides detailed investigations of MEPH’s and its primary metabolite nor-mephedrone’s (nor-MEPH) pharmacokinetics and bio-distribution to four different substrates (serum, brain, lungs and liver), as well as comparative analysis of their effects on locomotion (open field test, OFT) and sensorimotor gating (prepulse inhibition of acoustic startle reaction, PPI ASR). Further, in order to mimic the crowded condition where MEPH is typically taken (e.g., clubs), the acute effect of MEPH on thermoregulation in singly- and group-housed rats was evaluated. Pharmacokinetics of MEPH and nor-MEPH after MEPH (5 mg/kg, sc.) were analyzed over eight hours using liquid chromatography with mass spectrometry. MEPH (2.5, 5 or 20 mg/kg, sc.) and nor-MEPH (5 mg/kg, sc.) were administered five or 40 minutes before the behavioral testing in the OFT and PPI ASR; locomotion and its spatial distribution, ASR, habituation and PPI itself were quantified. The effect of MEPH on rectal temperature was measured after 5 and 20 mg/kg, sc. Both MEPH and nor-MEPH were detected in all substrates, with the highest levels detected in lungs. Mean brain: serum ratios were 1: 1.19 (MEPH) and 1: 1.91 (nor-MEPH), maximum concentrations were observed at 30 min; at two and four hours after administration, nor-MEPH concentrations were higher compared to the parent drug. Whilst neither of the drugs disrupted PPI, both increased locomotion and affected its spatial distribution. The effects of MEPH were dose-dependent, rapid and short-lasting, and the intensity of locomotor stimulant effects was comparable between MEPH and nor-MEPH. Despite the disappearance of behavioral effects within 40 min after administration, MEPH induced rectal temperature elevations that persisted for three hours even in singly-housed rats. To conclude, we observed a robust, short-lasting and most likely synergistic stimulatory effect of both drugs which corresponded to brain pharmacokinetics. The dissociation between the duration of behavioral and hyperthermic effects is indicative of the possible contribution of nor-MEPH or other biologically active metabolites. This temporal dissociation may be related with the risk of prolonged somatic toxicity when stimulatory effects are no longer present.